2017
DOI: 10.1126/sciimmunol.aan0368
|View full text |Cite
|
Sign up to set email alerts
|

T fr cells lack IL-2Rα but express decoy IL-1R2 and IL-1Ra and suppress the IL-1–dependent activation of T fh cells

Abstract: Follicular regulatory T (T) cells from lymph node germinal centers control follicular helper T (T) cell-dependent B cell activation. These scarce cells, often described and purified as CD25 cells, are thought to be derived from thymic regulatory T (T) cells. However, we observed that mouse T cells do not respond to interleukin-2 (IL-2), unlike T cells. Stringent immunophenotyping based on B cell lymphoma 6 (Bcl6), programmed cell death protein 1 (PD-1), and CXCR5 expression revealed that T cells are actually C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 75 publications
(88 reference statements)
10
135
1
Order By: Relevance
“…Interestingly, while microscopy suggested that essentially all the Tfr in the B-cell follicle and GC itself were CD25 + , flow cytometry analysis in the same report demonstrates that PD-1 hi Tfr express significantly less CD25 than PD-1 int or negative Tfr (CD25 MFI 616 ± 96 vs. 1101 ± 121.4, p = 0.0074 unpaired t -test), and also display a bimodal expression of CD25 with a significant fraction appearing to be CD25 lo/− (34). This is in keeping with two previous reports that suggested that the most highly-differentiated PD-1 hi CXCR5 hi BCL6 + Tfr in human tonsils also downregulate CD25 (25, 26). Importantly, however, while PD-1 hi Tfr do appear to be enriched in the GC itself, they are extremely rare, with only around 3% of Tregs in the mLN matching this description (34).…”
Section: Tregs and Tfr Cellssupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, while microscopy suggested that essentially all the Tfr in the B-cell follicle and GC itself were CD25 + , flow cytometry analysis in the same report demonstrates that PD-1 hi Tfr express significantly less CD25 than PD-1 int or negative Tfr (CD25 MFI 616 ± 96 vs. 1101 ± 121.4, p = 0.0074 unpaired t -test), and also display a bimodal expression of CD25 with a significant fraction appearing to be CD25 lo/− (34). This is in keeping with two previous reports that suggested that the most highly-differentiated PD-1 hi CXCR5 hi BCL6 + Tfr in human tonsils also downregulate CD25 (25, 26). Importantly, however, while PD-1 hi Tfr do appear to be enriched in the GC itself, they are extremely rare, with only around 3% of Tregs in the mLN matching this description (34).…”
Section: Tregs and Tfr Cellssupporting
confidence: 93%
“…In contrast, in the context of a primarily self-antigen-driven response, Tfr may play a more active role directly controlling GC B-cell and Tfh cell numbers. This may be because Tfr have a more self-skewed TCR repertoire, respond better to vaccination with self-antigens rather than foreign antigens, and do not appear to require recognition of the same antigen as a particular Tfh cell in order to suppress it (25, 46, 47). We also previously demonstrated that while short-term depletion of Tregs/Tfr is effective at enhancing antigen-specific Tfh formation following vaccination with a foreign antigen, longer-term depletion of Tregs further increased the total number of Tfh but also reduced the absolute number of antigen-specific Tfh (12).…”
Section: The In Vivo Role Of Tfr and Contribution Of Tregs To Humoralmentioning
confidence: 99%
See 2 more Smart Citations
“…35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs. 35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs.…”
Section: Cd25/il-2 Axis In Tfr-cell Responsesmentioning
confidence: 99%